2022
DOI: 10.1371/journal.pone.0277611
|View full text |Cite
|
Sign up to set email alerts
|

Childhood exposures to environmental chemicals and neurodevelopmental outcomes in congenital heart disease

Abstract: Background Children with congenital heart defects have an increased risk of neurodevelopmental disability. The impact of environmental chemical exposures during daily life on neurodevelopmental outcomes in toddlers with congenital heart defects is unknown. Methods This prospective study investigated the impacts of early childhood exposure to mixtures of environmental chemicals on neurodevelopmental outcomes after cardiac surgery. Outcomes were assessed at 18 months of age using The Bayley Scales of Infant an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Last, no standard pre-or perioperative assessment of baseline neurologic abnormalities was performed; these data were not collected as part of the primary study. 12 conclusions In infants undergoing corrective and palliative surgery for major congenital heart disease, cumulative volatile anesthetic exposures were not associated with lower neurodevelopmental assessment scores at 18-month follow-up after adjusting for nonmodifiable patient factors and length of stay. These findings contrast with studies that have shown volatile anesthetic exposure to be associated with worse neurodevelopmental outcomes in infants.…”
Section: Anesthesia and Neurodevelopment In Infantsmentioning
confidence: 79%
See 4 more Smart Citations
“…Last, no standard pre-or perioperative assessment of baseline neurologic abnormalities was performed; these data were not collected as part of the primary study. 12 conclusions In infants undergoing corrective and palliative surgery for major congenital heart disease, cumulative volatile anesthetic exposures were not associated with lower neurodevelopmental assessment scores at 18-month follow-up after adjusting for nonmodifiable patient factors and length of stay. These findings contrast with studies that have shown volatile anesthetic exposure to be associated with worse neurodevelopmental outcomes in infants.…”
Section: Anesthesia and Neurodevelopment In Infantsmentioning
confidence: 79%
“…As previously demonstrated, nonmodifiable patient factors such as race and presence of a genetic anomaly were associated with lower neurodevelopmental scores at 18-month follow-up. 12 We specifically focused this analysis on a patient population that experiences a substantial burden of cumulative anesthetic and sedative exposures early in life, as a meta-analysis of animal and human data suggested a dose dependency of deleterious outcomes. 23 In accordance with these findings, infants in this study were exposed to substantial cumulative anesthetic doses and considerable polypharmacy during perioperative and intensive care, with all receiving an inhaled anesthetic and a majority being exposed to opioids, ketamine, benzodiazepines, and barbiturates by 18 months of age.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations